Professional Competence of Arabic Language Teachers at Madaniyah Mataram High School West Nusa Tenggara - Mohammad Zaki (Fakultas Agama Islam Universitas Billfath, 2023)
The purpose of this study was to determine the professional competence of Arabic teachers and the efforts made to develop the potential of Arabic teachers at SMA Madaniyah Mataram, NTB. In this study, researchers used a qualitative approach. Primary sources were collected from Arabic teachers in terms of their professional competence. Secondary sources are collected from the principal or the school. Data collection techniques using observation, interviews, and documentation. The results of the study show that the professional competence of Arabic language teachers at Al-Madaniya School shows indicators of teacher professional competence: 1) Teacher professional competence, Teacher Professional Competency Index categories: (a) Material proficiency, structure, concepts and patterns of thinking in scholarships that support Arabic Adequate quality materials, (b) Adequate basic proficiency and Arabic language proficiency standards (c) Development of creative Arabic teaching materials minus Arabic (d) Developing professionalism on an ongoing basis by carrying out reflective work that is graded Adequate quality, and (e ) the use of ICT for communication and self-development is in the minus quality category. 2) Efforts to increase the professionalism of Arabic teachers at Madaniyah High School Mataram West Nusa Tenggara are as follows: namely courses, training, seminars, promotional workshops, control and efforts of teachers to improve their professional competence, follow and learn knowledge related to knowledge or methods or teaching and learning processes in general